2017
DOI: 10.29252/ijrm.15.4.231
|View full text |Cite|
|
Sign up to set email alerts
|

Pregnancy outcome of “delayed start” GnRH antagonist protocol versus GnRH antagonist protocol in poor responders: A clinical trial study

Abstract: Background:Management of poor-responding patients is still major challenge in assisted reproductive techniques (ART). Delayed-start GnRH antagonist protocol is recommended to these patients, but little is known in this regards.Objective:The goal of this study was assessment of delayed-start GnRH antagonist protocol in poor responders, and in vitro fertilization (IVF) outcomes.Materials and Methods:This randomized clinical trial included sixty infertile women with Bologna criteria for ovarian poor responders wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
(42 reference statements)
2
8
1
4
Order By: Relevance
“…Similarly, Maged et al; in a first randomized clinical trial on 160 patients with POR diagnosis showed that the delayed start protocol improved cycle outcome by reducing the total dose of used gonadotropin, improving estradiol levels (E 2 ) and endometrial thickness on the day of hCG administration and increasing the total number of retrieved and mature oocytes [9]. However, Aflatoonian et al in a randomized pilot study on 60 POR failed to show any significant difference between this new strategy and routine antagonist protocol [10]; although the non-significant results may relate to small sample size. In our study, the clinical pregnancy rate in both study and control groups were low (8.7% vs. 7.1%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Maged et al; in a first randomized clinical trial on 160 patients with POR diagnosis showed that the delayed start protocol improved cycle outcome by reducing the total dose of used gonadotropin, improving estradiol levels (E 2 ) and endometrial thickness on the day of hCG administration and increasing the total number of retrieved and mature oocytes [9]. However, Aflatoonian et al in a randomized pilot study on 60 POR failed to show any significant difference between this new strategy and routine antagonist protocol [10]; although the non-significant results may relate to small sample size. In our study, the clinical pregnancy rate in both study and control groups were low (8.7% vs. 7.1%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cakmak et al, in a retrospective study introduced a novel approach with delaying the start of COS along with GnRH antagonist pretreatment for 7 days after estrogen priming for further suppression of endogenous FSH during the early follicular phase, resulting in more FSH-responsive follicles and thus improving synchronous follicular development [8]. Also, two clinical trials have examined this strategy and reported controversial results [9, 10]. The present randomized clinical trial was designed to compare the efficacy of delayed-start GnRH antagonist protocol versus GnRH antagonist protocol in patients with poor ovarian response diagnosis on the basis of Bologna criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoonian and colleagues in a clinical trial concluded that in poor responders delayed-start protocol slightly but not significantly improves pregnancy and implantation rate. They compared conventional antagonist protocol with delayed-start protocol ( 16 ). In our study delayed protocol was compared with microdose flare to find a suitable ART protocol in poor responders and the results indicated that the number of retrieved oocytes, mature oocytes, number of 2 PN and implantation rate were significantly higher in delayed antagonist group.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of various developmental stages of antral follicles due to different FSH receptor levels can cause different susceptibility to FSH and thus lead to heterogeneous follicular development. The resulting size heterogeneity causes asynchronous growth and poor follicular response at the beginning of COH treatment [5][6][7]. Estradiol is the main hormone involved in the negative regulation of FSH.…”
Section: Introductionmentioning
confidence: 99%